HUBUNGAN PERSEPSI PASIEN TENTANG MUTU PELAYANAN PERAWAT DENGAN LOYALITAS PASIEN DI PUSKESMAS LETWARU KECAMATAN AMAHAI - Dewi Arwini Bugis; Markus Falentino Lekilawa (Pasapua Health Journal, 2021)
Introduction: Understanding Perception as a process of how one selects, organizes and interprets inputs of information to create a meaningful overall picture. Methods: This research is a type of quantitative research using a cross sectional study approach. The sampling technique in this study used the total sampling method, the sample in this study were 30 respondents aged 18-60 years. Results: The results of this study show that there is a relationship between patient perceptions of the quality of nursing services and patient loyalty at the Letwaru Public Health Center, Amahai District, 2020. Conclusions: This research is expected to be input for nursing staff so that this research can become additional knowledge and improve the quality of nursing services for patients.